(untitled) (Revista Interdisciplinar Pensamento Científico, 2021)
The present study aims to foster respect for transgender people’s problems in the execution of deprivation of liberty sentences based on fundamental rights that govern the national legal system. Therefore, through a bibliographic review, it performs a historical journey of the prison system and gender issues to then reflect on the current reality of transgender people in prison. Therefore, what is perceived is a legislation of rights and principles that emphasize human dignity but that, in practice, perpetuate discriminatory stigmas and attitudes marked by violence against the transgender population. The portrayal of these practices is a high level of violence against the LGBT community outside and inside the prison, and especially in the latter, a topic in vogue in this work. To this end, it emphasizes the need for institutional information at the social, political, and legal level that contemplates practice constitutionally foreseen issues.